STUDENTS ERRORS IN CONSTRUCTING REPORTED SPEECH - Maria Gabrielis Gerhanawati; Deddy Sofyan; Istiqlaliah Nurul Hidayati (Journal of English Teaching and Linguistics Studies (JET Li), 2019)
ABSTRACTThe paper entitled “Students’ Errors in Constructing Reported Speech” is aimed to find out students’ errors in constructing reported speech. In constructing the research, the writer applies descriptive method to analyze students’ errors in constructing reported speech. The research was conducted to the third semester students of English Language Education Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. The writer uses purposive sampling in conducting this research and takes 15 from three classes who learn reported speech. The data were gained from three instruments: documentation, questionnaire and interview. The documentations were taken from students’ works, questionnaires were distributed to 15 students who became the participants of this research and interview was also done to the lecturer who teaches reported speech. The research finding shows that the students make errors in constructing reported speech. The writer finds out four types of error: they are omission, addition, misinformation and misordering. The result shows that most common error found in constructing reported speech in misinformation. The writer suggests that the students should do more exercises in constructing reported speech appropriately by paying attention more to the rules of sentence transformation, especially in tense’ changes.Keywords: Direct Speech, Reported Speech, Error, Error Analysis.